Teachers Characteristics and Students’ Performance Level in Senior Secondary School Financial Accounting - Omotayo, Bolarinwa Kayode (Journal of Empirical Studies, 2014)
The purpose of this study was to investigate the relationship that exists between teachers’ characteristics (qualification, years of experience) and students’ performance level in Senior Secondary School Financial Accounting. In doing this, the study investigated selected teachers characteristics and students performance level in Senior Secondary School Financial Accounting using correlation research design. The study was limited to Senior Secondary Schools in Ondo State. A total of 200 students were selected through purposive sampling technique to participate in the study. Two research questions were raised and answered. Two validated instruments titled; Teachers Qualification and Experience Questionnaire (TQEQ) and Financial Accounting Achievement Test (FAAT) were used for data collection. The Pearson Product Moment Correlation was the major statistical tool employed for data analysis. Findings revealed that a positive relationship exists between teachers’ characteristics (Qualification and Experience) and performance level of the students in Financial Accounting. It is recommended among others that capacity development scheme should be put in place for teachers with the aim of enhancing their efficiency and improving students’ performance.